Forest plantation in peninsular Malaysia / Norini Abd. Samad - Abd. Samad, Norini (2002)
Forestry in Peninsular Malaysia consists from many types of forest. One of it is forest plantation which is a man-made forest. This means, it is unnatural forest. Forest Plantation is established to maintain self-sufficiency of forest resource and timber supply in Peninsular Malaysia, because of the shortage of the natural forest. From the history of plantation which began in 1887 until now, it showed that forest plantation is always built on with back-up from research and studies. Otherwise, the choice of a good species is important. And it is based on specifics criteria. Besides that we must take seriously about the management aspects of the species.